A Study on the Impact of Implementation of Strategic Hr Practices on Organization Performance - Sam, Annie; Shameem, A. (International Journal of Psychosocial Rehabilitation, 2020)
--- Strategic HRM being a relatively topic deals with the drastic transformation of the HR function in order to make it more acceptable as a business partner and is essentially connected with the way in which human resource management professionals could play a vital role in improving organisational performance. Research has identified that HR practices implemented through business partnership resulted in a 47% jump in shareholder value (Bruce Pfau & Ira Kay, 2002). The objectives of this study are to know if the relationship between SHRM implementation and organizational performance is affected by firm’s size and age and to analyze the relationship between SHRM implementation and the organizational performance. The study is descriptive in nature and has made use of a questionnaire to collect primary data required for the study. The results of the study have shown interesting findings which prove that both number of years in existence and size of the organization have a role to play with respect to implementation of strategic HR and the impact of strategic HR on organisational performance.